Comparative Analysis of the Level of Development of Entrepreneurial Competencies among Students in Russia and the Czech Republic - Pesha Anastasiya (SHS Web of Conferences, 2021)
The role of universities in the development of entrepreneurship is increasing. Within this context, universities are introducing specialized programs and disciplines aimed at developing students’ innovative and entrepreneurial competencies. This article presents the results of a comparative analysis of the level of development of students’ entrepreneurial competencies in Russia and the Czech Republic. To implement the key task, the authors analysed approaches to the classification of entrepreneurial competencies. On the basis of relevance and objectivity, the authors selected the EntreComp classification from 2016, which subsequently formed the basis for the developed methodological tools for the empirical research. The method was tested in three universities in the Russian Federation and one in the Czech Republic. The total number of participants was 436. The results of the analysis of the entrepreneurial competencies revealed significant statistical differences between the respondents from the two countries for 10 out of 15 evaluated competencies. At the same time, 68% of respondents in the Russian Federation and 64% in the Czech Republic were found to have an advanced level of development of one entrepreneurial competence. This fact is indicative of the similarity of the vast majority of the final results for the respondents from both countries and confirms the hypothesis that most students participating in the test did not have a lower than average level of competence development. The results of the study may be of interest to scientists and practitioners who study the assessment and development of entrepreneurial competencies in students and specialists.